Risk of new‐onset heart failure in patients using sitagliptin: a population‐based cohort study. Issue 5 (25th August 2015) - Eurich, D. T.; Weir, D. L.; Simpson, S. H.; Senthilselvan, A.; McAlister, F. A.
Abstract: Aims: To examine whether patients using sitagliptin at the time of an acute coronary syndrome event are at increased risk of incident heart failure compared with those not exposed. Methods: Using US claims data, people with diabetes without a history of heart failure in the 3 years before hospitalization for acute coronary syndrome were identified for the period 2004 to 2010. We used a nested case–control design, whereby cases were patients who developed incident heart failure <30 days after admission to hospital for acute coronary syndrome and were matched by age and sex with up to 10 controls with no heart failure. Subjects exposed or not exposed to sitagliptin in the 90 days before acute coronary syndrome admission were compared using conditional logistic regression after adjustment for clinical and laboratory data, healthcare utilization and propensity scores. Results: In total, 457 cases of heart failure developing de novo after diagnosis of acute coronary syndrome were matched to 4570 controls. The average age of the subjects was 55 years and 65% were male. Overall, 11 of 147 (7%) people exposed to sitagliptin developed heart failure compared with 446 of the 4880 people not exposed (9%, adjusted odds ratio 0.75, 95% CI 0.38–1.46; P =0.40). Sitagliptin exposure before acute coronary syndrome was not associated with an increased risk of death or heart failure combined (7% vs 9%, adjusted odds ratio 0.66, 95% CI 0.34–1.28). Conclusions: In our sample of patients who are at high risk of heart failure after acute coronary syndrome, sitagliptin exposure was not associated with an increased risk of de novo heart failure. What's new?: Significant debate exists with regard to the risk associated with dipeptidyl peptidase‐4 inhibitors and new‐onset heart failure. Our study suggests that, among patients in a high‐risk group, sitagliptin is not associated with de novo heart failure.